Classification of cavernous internal carotid artery tortuosity: a predictor of procedural complexity in Pipeline embolization. (4th July 2014) - Lin, Li-Mei; Colby, Geoffrey P; Jiang, Bowen; Uwandu, Chiedozie; Huang, Judy; Tamargo, Rafael J; Coon, Alexander L
Abstract : Background: Flow diverters are increasingly used for the treatment of intracranial aneurysms. Understanding cavernous internal carotid artery (cICA) tortuosity may help to predict procedural complexities of deploying flow diverters. Methods: Pipeline embolization device (PED) neurointerventions for ICA aneurysms proximal to the ICA termination were reviewed. Cavernous ICA tortuosity was measured as a ratio D/AP, where D=height difference of the anterior and posterior genus, AP=sum of the angles of the anterior (A) and posterior (P) genus. Four types of cICA tortuosity were proposed. An analysis of variance regression and Fisher's exact test were performed to analyze differences among the types. Results: Cavernous ICA tortuosity was categorized into minimal (type I, n=28), moderate (type II–III, n=29), and severe (type IV, n=26). The groups were comparable for patient age (mean ± SEM years, type I: 55.6±10.4, II–III: 56.4±14.4, IV: 55±12.8) and aneurysm size (mean±SEM mm, type I: 6.25±3.5, II–III: 7.6±4.9, IV: 9.11±4.9). Analysis of variance demonstrated significant differences in procedural fluoroscopy time (mean ± SEM min, type I: 29.8±8.4, II–III: 44.9±34.1, IV: 52.6±17.2, p<0.005) and mean ± SEM D/AP (type I: 0.008±0.0008, II–III: 0.141±0.07, IV: 0.482±0.365, p<0.0001). Procedural complexity was also statistically significant (p<0.005) with 4%, 28%, and 35% of cases in types I, II–III, and IV, respectively, requiring intraprocedural PED removal or balloon post-processing of the implanted PED. Conclusions: We propose a classification system for cICA tortuosity based on measurements of the anterior and posterior genu geometry. This classification correlates strongly with markers of PED procedural complexity and may be helpful in pre-procedure prognostication.